Caries prevalence and treatment needs of rural school children in Chidambaram Taluk, Tamil Nadu, South India - Saravanan S; Kalyani V; Vijayarani M; Jayakodi P; Felix JWA; Arunmozhi P; Krishnan V; Sampath Kumar P (Wolters Kluwer Medknow Publications, 2008)
Objective: To obtain information on caries prevalence and treatment needs of children aged 5-10 years to plan appropriate dental care services in rural areas. Materials and Methods: Children studying in all the primary schools (six schools) in the field practice area of the Rural Health Centre of the Faculty of Medicine, Annamalai University, Chidambaram, were surveyed. Each child was clinically examined in the schools by calibrated examiners. Dental caries was assessed using diagnostic criteria recommended by WHO (1997). The chi-square test and two-way analysis of variance were used for statistical analysis. Results: Five hundred and eight 5-10 year-old school children (247 boys and 261 girls) were surveyed. Caries prevalence was 71.7 and 26.5% in primary and permanent dentition, respectively. The mean dmft and decayed missing filled tooth (DMFT) scores were 3.00 and 0.42 respectively. The mean dmft decreased with age ( P < 0.01) whereas the mean DMFT increased with age ( P < 0.001). Although the mean dmft scores were not statistically significant different for the two sexes, the mean DMFT score was found to be higher among girls than among boys ( P < 0.02). The entire dmft/DMFT value represented the ′decay′ component only. There was a strong need for single surface restorations (60.6%). In the WHO index age (5-6 years), the caries prevalence was 70.2% (29.8% caries-free) with a mean dmft value of 3.54 ± 3.71. Conclusion: Dental caries is a significant public health problem in this population. An extensive system to provide primary oral health care has to be developed in the rural areas of India.